Intron mis-splicing: no alternative? - Roy, Scott William (BioMed Central, 2008)
A recent report reveals widespread mis-splicing of RNA transcripts in eukaryotes, with mis-spliced RNA destroyed by nonsense-mediated mRNA decay. This striking inefficiency deepens the mystery of the proliferation and persistence of introns.